American Dog Tick, Dermacentor variabilis (Say) (Arachnida: Ixodida: Ixodidae) - Wai-Han Chan; Phillip E. Kaufman (EDIS)
EENY-443, a 7-page fact sheet by Wai-Han Chan and Phillip E. Kaufman, is part of the Featured Creatures Collection. It describes this tick commonly found on dogs as an adult — its distribution, description, life cycle, seasonality, medical and veterinary importance, removal, and management. Includes references. Published by the UF Department of Entomology and Nematology, November 2008.